Effect of slightly elevated progesterone on hCG trigger day on clinical pregnancy rate in GnRH-ant IVF/ICSI cycles - Jing Zhao; Jie Hao; Bin Xu; Yonggang Wang; Yanping Li (BMC, 2022)
Abstract Background It was been agreed that significantly elevated progesterone level on the hCG trigger day have detrimental effect on clinical outcomes in IVF/ICSI cycles. However, few studies explored whether slightly elevated progesterone level also same impact on clinical outcomes. Methods We retrospectively studies the effect of slightly elevated progesterone level on outcomes of IVF/ICSI in GnRH-ant cycles. Propensity score matching was used to confounding variables. The women were divided into two groups according to the progesterone level: Group 1: < 1.0 ng/ml; Group 2: 1.0 ng/ml-1.5 ng/ml. Then compare the clinical pregnancy rate (CPR) between the two groups. Result A total of 847 IVF/ICSI cycles were included in the present study. The average CPR per transfer cycle was 51.7%. CPR of group 1 was 55.22%, significantly higher than that of group 2 (40.66%, P = 0.013). Progesterone level on the day of hCG injection was further evaluated at threshold increments of 0.1 ng/ml, and the CPR was decreased dramatically once the progesterone level higher than 1.4 ng/ml. Conclusion The slight elevation progesterone level on the hCG trigger day may have a negative effect on the clinical pregnancy in GnRH-ant cycles. In the case of progesterone > 1.4 ng/ml on the hCG injection day, freeze-all strategy was recommended. Summary The present retrospective study aimed to evaluate the effect of slightly elevated progesterone (1.0 ng/ml ~ 1.5 ng/ml) on outcomes of IVF/ICSI in GnRH-ant cycles. Slightly elevated progesterone level leaded to significant lower clinical pregnancy rate (CPR) that that of group with normal progesterone level (40.66% vs. 55.22%, P = 0.013). The CPR was decreased dramatically once the progesterone level higher than 1.4 ng/ml. So slightly elevated progesterone level on the trigger day may have a negative effect on the clinical pregnancy in GnRH-ant cycles. In the case of progesterone > 1.4 ng/ml on the hCG injection day, freeze-all strategy was recommended.